Graphite material recovery method, graphite material and application thereof
Through the steps of calcining, pickling, prelithiation, coating and carbonization, waste graphite negative electrode materials are efficiently recovered, solving the problem of insufficient purity and reusability of graphite recovery in the prior art, and achieving significant improvement in graphite material performance and excellent electrochemical performance of lithium-ion batteries.
Patent Information
- Application Number
- CN202411998078.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The existing graphite recycling methods have shortcomings in removing impurities and structural repair, resulting in poor purity and low reusability of the recycled graphite material.
Calcination, pickling, prelithiation, coating and carbonization steps are adopted to efficiently recover waste graphite negative electrode materials. Calcination removes electrolyte and other components, acid washing removes impurities and doped with boron, prelithiation improves the binding of lithium and boron, and coats and carbonizes to form a cladding repair structure.
It significantly improves the overall performance of graphite materials, improves its capacity and first-term effect for lithium-ion batteries, and has excellent electrochemical properties.
Smart Images

Figure BDA0005225914210000121
Abstract
Description
Technical Field
[0001] The invention relates to a graphite material recovery method, graphite material and application thereof. Background Art
[0002] With the rapid development of society, people's demand for energy is increasing day by day. At present, 85% of the world's energy comes from non-renewable energy sources such as oil, coal, and natural gas. Faced with the growth of energy demand and the consumption of non-renewable energy, people gradually find that the rational use of non-renewable energy and the development of other renewable energy sources are particularly important. Lithium-ion batteries are currently widely used in various fields due to their advantages such as high energy density, light weight, small size, and mature technology. Faced with the rising demand for lithium-ion batteries, people have to gradually face the problem of recycling and processing lithium-ion batteries after failure. How to efficiently recycle and process the various component materials of the battery is a new challenge that researchers will face in the future.
[0003] Currently, commercial lithium-ion batteries are mainly composed of positive electrodes, negative electrodes, diaphragms and other precision components. For the positive electrodes containing more valuable metals in waste batteries, there are currently many mature solutions to recycle the metals contained in them for secondary use. However, due to unfavorable factors such as environmental pollution and high cost involved in the processing process, negative electrode materials are currently less used in industrial applications. However, with the continuous consumption of graphite resources and the increase in strategic value, the necessity of recycling graphite negative electrodes is also growing.
[0004] There are currently several methods for recycling graphite negative electrodes: flotation, acid-base purification, and high-temperature heat treatment. Among them, physical purification methods such as flotation are simple and direct, but since physical methods cannot remove chemical components such as binders, thickeners, and electrolytes in the pole pieces, the recovered graphite has a relatively poor purity and a low degree of reusability. High-temperature heat treatment usually has a temperature in the range of 2000℃-3000℃, which also has the effect of deep purification, but high energy consumption and industrial safety also limit the industrial promotion and application of this method.
[0005] For example, Chinese patent application CN 118099582 A discloses a waste graphite regeneration and repair technology, which sequentially treats waste graphite with ultrasound, drying, plasma ball milling and roasting to finally obtain regenerated graphite negative electrode powder; although the process of this method is simple and fast, it has limited treatment capabilities for waste graphite impurities and its structural repair is imperfect.
[0006] Accordingly, in the existing graphite recovery methods, when removing impurities and repairing structures, for example, Chinese patent application CN115448308 A discloses a method for removing impurities and repairing waste lithium battery negative electrode powder. The method uses an inorganic acid to pickle and calcine the waste graphite and then uses a coating agent to repair the graphite; the method plays a certain role in improving the performance of the waste graphite, but the overall performance of the recovered graphite is still limited.
[0007] Therefore, there is an urgent need for an efficient method for recovering graphite materials from waste graphite negative electrodes to comprehensively improve the performance of the resulting graphite materials. Summary of the invention
[0008] In order to solve the above technical defects existing in the prior art, the present invention provides a graphite material recycling method, graphite material and its application. The recycling method can effectively recycle graphite in waste batteries, reduce impurities, and effectively repair its overall structure; the overall performance of the obtained graphite material is significantly improved, and it has excellent electrochemical performance after being used in lithium-ion batteries.
[0009] To achieve the above purpose, the present invention adopts the following technical solution.
[0010] The present invention provides a graphite material recovery method, which comprises the following steps:
[0011] S1. calcining graphite negative electrode powder of waste batteries to obtain a first precursor;
[0012] S2, washing the first precursor with an acid solution to obtain a second precursor;
[0013] Wherein, the acid solution comprises boric acid and an oxidant;
[0014] S3, pre-lithiating the second precursor with a lithium salt to obtain a third precursor;
[0015] S4. Coating the third precursor with a coating agent and carbonizing it to obtain the graphite material.
[0016] In the present invention, the calcination step can increase the pores in the graphite and provide more active sites while removing components such as the electrolyte, the binder, and the conductive agent remaining in the graphite negative electrode; in the pickling step, when washing with an acid solution containing boric acid and an oxidant, the oxidant can activate the inactivated lithium ions remaining inside and on the surface of the waste graphite to the greatest extent, thereby realizing the reuse of the inactivated lithium; while effectively removing impurities by pickling, more boron elements can be doped, thereby forming lithium boron oxide with the lithium on the graphite surface, thereby reducing the loss of lithium, and further improving the combination of lithium and boron after pre-lithiation, thereby storing more active lithium; and finally, after coating and carbonization to form a coating layer, the collapsed structure of the entire surface is repaired, thereby improving the overall performance of the obtained graphite material.
[0017] In the present invention, in step S1, the graphite negative electrode powder may be negative electrode powder obtained by conventional scraping from a conventional graphite negative electrode in the art.
[0018] In some embodiments, in step S1, the waste batteries include waste lithium-ion batteries, such as one or more of 10440 batteries, 21700 batteries and 26650 batteries.
[0019] In some embodiments, in step S1, the calcination is performed under an inert atmosphere.
[0020] In some preferred embodiments, the inert atmosphere comprises nitrogen and / or argon.
[0021] In some embodiments, in step S1, the calcination includes a temperature rising stage and a temperature keeping stage.
[0022] In some preferred embodiments, the heating rate in the heating stage is 5-10°C / min.
[0023] In some preferred embodiments, the temperature of the insulation stage is 200-600°C, such as 450°C.
[0024] In some preferred embodiments, the insulation stage lasts for 60-200 min, such as 180 min.
[0025] In the present invention, in step S2, when the doped boron is washed with an acid solution containing boric acid, part of the carbon atoms on the surface of the graphite can be replaced to form boron-carbon bonds and boron-carbon-oxygen bonds with carbon, thereby providing more active sites for the graphite, combining lithium and enhancing the electronic conductivity of the obtained graphite material.
[0026] In some embodiments, in step S2, the acid solution is prepared by mixing a mixed acid and an oxidant, and the mixed acid includes boric acid.
[0027] In some preferred embodiments, in the mixed acid, the volume proportion of the boric acid is not less than 70%.
[0028] In some preferred embodiments, the mixed acid further comprises one or more of hydrochloric acid, nitric acid and sulfuric acid.
[0029] In some preferred embodiments, the molar concentration of the acid in the mixed acid is 0.4-2 mol / L, such as 1 mol / L or 1.5 mol / L.
[0030] In some embodiments, in step S2, the oxidant includes hydrogen peroxide and / or potassium permanganate.
[0031] In some embodiments, in step S2, the mass ratio of the oxidant to the acid solution is (0.02-0.6):1, such as 0.1:1 or 0.2:1.
[0032] In some embodiments, in step S2, the liquid-to-solid ratio of the acid solution and the first precursor is (4-6):1, for example, 5:1.
[0033] In some embodiments, in step S2, the pickling temperature is 60-100°C.
[0034] In some embodiments, in step S2, the acid washing time is 4-6 hours.
[0035] In some embodiments, in step S2, the acid washing includes the step of stirring and mixing the first precursor and the acid solution.
[0036] In some embodiments, in step S2, the acid washing further includes the steps of solid-liquid separation, washing, drying and screening.
[0037] In some preferred embodiments, the solid-liquid separation is performed by suction filtration.
[0038] In some preferred embodiments, the washing is performed with water.
[0039] In some preferred embodiments, the screening is performed using a sieve; the mesh size of the sieve is, for example, 300 mesh.
[0040] In some embodiments, in step S3, the lithium salt includes one or more of lithium carbonate, lithium oxalate, lithium chloride and lithium nitrate.
[0041] In some embodiments, in step S3, the particle size of the lithium salt is 200-800 nm.
[0042] In some embodiments, in step S3, the mass ratio of the lithium salt to the second precursor is (0.01-0.06):1, for example 0.02:1.
[0043] In some embodiments, in step S3, the pre-lithiation includes the step of mixing the second precursor and the lithium salt.
[0044] In some preferred embodiments, the mixing is performed by ball milling. It has been found that in the graphite recovery of the present invention, during pre-lithiation, only simple mechanical external forces such as ball milling are required to effectively improve the binding rate of boron and lithium through physical structural reconstruction, thereby further improving the overall performance of the obtained graphite.
[0045] The rotation speed of the ball mill is preferably 200-600 r / min, such as 300 r / min.
[0046] In some embodiments, in step S3, the pre-lithiation time is 0.5-4 h, such as 1 h or 2 h.
[0047] In some embodiments, in step S4, the coating agent includes one or more of polyacrylonitrile, polytetrafluoroethylene and dopamine, preferably polyacrylonitrile. Studies have shown that when polyacrylonitrile is used as a coating agent, a structure similar to a graphene coating layer can be formed after carbonization. Compared with a conventional carbon coating layer, the overall structural repair effect is better, thereby resulting in better overall performance of the obtained graphite material.
[0048] In some embodiments, in step S4, the mass ratio of the capping agent to the third precursor is (0.01-0.1):1, for example, 0.02:1 or 0.06:1.
[0049] In some embodiments, in step S4, the coating includes the step of mixing the third precursor with the coating agent in a solvent.
[0050] In some preferred embodiments, the solvent includes one or more of deionized water, ethanol and DMF.
[0051] In some preferred embodiments, the solid content after mixing is 40-60 wt%, such as 50 wt%.
[0052] In some preferred embodiments, the mixing is performed by stirring.
[0053] In some preferred embodiments, the mixing time is 2-6 hours.
[0054] In some preferred embodiments, the mixing temperature is 60-100°C.
[0055] In some embodiments, in step S4, the coating further includes a pre-oxidation step, which can further increase the pores and provide more active sites, so that when actually applied to the battery, the first efficiency, capacity and other performance can be further improved.
[0056] In some preferred embodiments, the pre-oxidation is performed in an oven.
[0057] In some preferred embodiments, the pre-oxidation temperature is 200-450°C, such as 300°C.
[0058] In some preferred embodiments, the pre-oxidation time is not less than 6 hours.
[0059] In some preferred embodiments, the pre-oxidation further comprises a grinding step.
[0060] In some embodiments, in step S4, the carbonization includes a temperature rising stage and a temperature keeping stage.
[0061] In some preferred embodiments, the heating rate in the heating stage is 2-6°C / min, such as 5°C / min.
[0062] In some preferred embodiments, the temperature of the insulation stage is 1000-1300°C, for example 1200°C.
[0063] In some preferred embodiments, the insulation stage lasts for 4-6 hours.
[0064] In some embodiments, in step S4, the carbonization is performed under an inert atmosphere.
[0065] In some preferred embodiments, the inert atmosphere comprises nitrogen and / or argon.
[0066] The present invention also provides a graphite material, which is prepared by the graphite material recovery method as described above.
[0067] In some embodiments, the graphite material includes a graphite matrix, a graphene-like coating layer, elemental lithium and lithium boron oxide; the lithium boron oxide is distributed on the surface of the stone mill matrix.
[0068] The present invention also provides a use of the graphite material as described above in an electrochemical device.
[0069] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0070] The reagents and raw materials used in the present invention are commercially available.
[0071] The positive and progressive effects of the present invention are:
[0072] The present invention effectively recovers graphite from waste batteries through specific calcination, pickling, pre-lithiation, coating and carbonization steps. The recycling method can effectively reduce impurities in the graphite while realizing the reuse of residual inactivated lithium and effectively repairing its overall structure; the overall performance of the obtained graphite material is significantly improved, and after being used in lithium-ion batteries, it has excellent capacity and initial efficiency. DETAILED DESCRIPTION
[0073] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0074] Example 1
[0075] The recycling of graphite materials is carried out in the following steps:
[0076] (1) Calcination: Waste graphite powder was directly scraped from the negative electrode sheet of a waste battery (cylindrical 10440 battery), and was heated to 450°C at a heating rate of 5°C / min in a nitrogen atmosphere and kept at this temperature for 180 min to obtain a first precursor.
[0077] (2) Acid pickling: The first precursor was added to a 60°C acid solution (prepared by mixing 1 mol / L boric acid and hydrogen peroxide, with the mass proportion of hydrogen peroxide being 10 wt%) at a liquid-to-solid ratio of 5:1, and the mixture was acid-picked with stirring for 4 h; then filtered and washed with water until the pH value was 7, dried in an oven at 100°C, and sieved using a 300-mesh sieve to obtain a second precursor.
[0078] (3) Pre-lithiation: Take 2 wt% (based on the mass of the second precursor) of nano-scale lithium carbonate (particle size of 200 nm), add it into a ball mill together with the second precursor, and ball-mill at a speed of 300 r / min for 1 h to obtain a third precursor.
[0079] (4) Coating and carbonization: 6 wt% (based on the mass of the third precursor) of liquid polyacrylonitrile is added to a magnetic stirrer together with the third precursor and an appropriate amount of deionized water (to make the solid content 50 wt%), and stirred at 60°C for 2 h until a viscous slurry is obtained. The slurry is then placed in an oven at 300°C for drying for 6 h, taken out and ground; the slurry is then placed in a tubular furnace and heated to 1200°C at a heating rate of 5°C / min in a nitrogen atmosphere, maintained at a constant temperature for 4 h, and cooled to room temperature to obtain the graphite material of this embodiment.
[0080] Example 2
[0081] (1) Calcination: Waste graphite powder was directly scraped from the negative electrode sheet of a waste battery (cylindrical 10440 battery), and was heated to 450°C at a heating rate of 5°C / min in a nitrogen atmosphere and kept at this temperature for 180 min to obtain a first precursor.
[0082] (2) Pickling: The first precursor was added to a 60°C acid solution (prepared by mixing 1 mol / L mixed acid (boric acid and nitric acid, wherein the volume proportion of boric acid is 70%) and hydrogen peroxide, and the mass proportion of hydrogen peroxide is 10 wt%) at a liquid-to-solid ratio (mass ratio) of 5:1, and stirred for pickling for 4 hours; then filtered and washed with water until the pH value was 7, dried in an oven at 100°C, and sieved using a 300-mesh sieve to obtain a second precursor.
[0083] (3) Pre-lithiation: Take 1 wt% (based on the mass of the second precursor) of nano-scale lithium carbonate (particle size of 200 nm), add it into a ball mill together with the second precursor, and ball-mill at a speed of 300 r / min for 1 h to obtain a third precursor.
[0084] (4) Coating and carbonization: 6 wt% (based on the mass of the third precursor) of liquid polyacrylonitrile is added to a magnetic stirrer together with the third precursor and an appropriate amount of deionized water (to make the solid content 50 wt%), and stirred at 60°C for 2 h until a viscous slurry is obtained. The slurry is then placed in an oven at 300°C for drying for 6 h, taken out and ground; the slurry is then placed in a tubular furnace and heated to 1200°C at a heating rate of 5°C / min in a nitrogen atmosphere, maintained at a constant temperature for 4 h, and cooled to room temperature to obtain the graphite material of this embodiment.
[0085] Example 3
[0086] (1) Calcination: Waste graphite powder was directly scraped from the negative electrode sheet of a waste battery (cylindrical 10440 battery), and was heated to 450°C at a heating rate of 5°C / min in a nitrogen atmosphere and kept at this temperature for 180 min to obtain a first precursor.
[0087] (2) Pickling: The first precursor was added to a 60°C acid solution (prepared by mixing 1.5 mol / L boric acid and hydrogen peroxide, with the mass proportion of hydrogen peroxide being 20 wt%) at a liquid-to-solid ratio of 5:1, and the mixture was pickled with stirring for 4 h; then the mixture was filtered and washed with water until the pH value was 7, dried in an oven at 100°C, and sieved using a 300-mesh sieve to obtain a second precursor.
[0088] (3) Pre-lithiation: Take 2 wt% (based on the mass of the second precursor) of nano-scale lithium carbonate (particle size of 200 nm), add it into a ball mill together with the second precursor, and ball-mill at a speed of 300 r / min for 2 h to obtain a third precursor.
[0089] (4) Coating and carbonization: 6 wt% (based on the mass of the third precursor) of liquid polyacrylonitrile is added to a magnetic stirrer together with the third precursor and an appropriate amount of deionized water (to make the solid content 50 wt%), and stirred at 60°C for 2 h until a viscous slurry is obtained. The slurry is then placed in an oven at 300°C for drying for 6 h, taken out and ground; the slurry is then placed in a tubular furnace and heated to 1200°C at a heating rate of 5°C / min in a nitrogen atmosphere, maintained at a constant temperature for 4 h, and cooled to room temperature to obtain the graphite material of this embodiment.
[0090] Example 4
[0091] (1) Calcination: Waste graphite powder was directly scraped from the negative electrode sheet of a waste battery (cylindrical 10440 battery), and was heated to 450°C at a heating rate of 5°C / min in a nitrogen atmosphere and kept at this temperature for 180 min to obtain a first precursor.
[0092] (2) Acid pickling: The first precursor was added to a 60°C acid solution (prepared by mixing 1 mol / L boric acid and hydrogen peroxide, with the mass proportion of hydrogen peroxide being 10 wt%) at a liquid-to-solid ratio of 5:1, and the mixture was acid-picked with stirring for 4 h; then filtered and washed with water until the pH value was 7, dried in an oven at 100°C, and sieved using a 300-mesh sieve to obtain a second precursor.
[0093] (3) Pre-lithiation: Take 2 wt% (based on the mass of the second precursor) of nano-scale lithium carbonate (particle size of 200 nm), add it into a ball mill together with the second precursor, and ball-mill at a speed of 300 r / min for 1 h to obtain a third precursor.
[0094] (4) Coating and carbonization: Take 2 wt% (based on the mass of the third precursor) of liquid polyacrylonitrile, add it together with the third precursor and an appropriate amount of deionized water (to make the solid content 50 wt%) into a magnetic stirrer, stir it at 60°C for 2 h until it becomes a viscous slurry, then put it into an oven at 300°C for drying for 6 h, take it out and grind it; then place it in a tubular furnace, and in a nitrogen atmosphere, heat it to 1200°C at a heating rate of 5°C / min, keep it at a constant temperature for 4 h, and cool it to room temperature to obtain the graphite material of this embodiment.
[0095] Example 5
[0096] (1) Calcination: Waste graphite powder was directly scraped from the negative electrode sheet of a waste battery (cylindrical 10440 battery), and was heated to 450°C at a heating rate of 5°C / min in a nitrogen atmosphere and kept at this temperature for 180 min to obtain a first precursor.
[0097] (2) Acid pickling: The first precursor was added to a 60°C acid solution (prepared by mixing 1 mol / L boric acid and hydrogen peroxide, with the mass proportion of hydrogen peroxide being 10 wt%) at a liquid-to-solid ratio of 5:1, and the mixture was acid-picked with stirring for 4 h; then filtered and washed with water until the pH value was 7, dried in an oven at 100°C, and sieved using a 300-mesh sieve to obtain a second precursor.
[0098] (3) Pre-lithiation: Take 2 wt% (based on the mass of the second precursor) of nano-scale lithium carbonate (particle size of 200 nm), add it into a ball mill together with the second precursor, and ball-mill at a speed of 300 r / min for 1 h to obtain a third precursor.
[0099] (4) Coating and carbonization: 10 wt% (based on the mass of the third precursor) of liquid polyacrylonitrile is added to a magnetic stirrer together with the third precursor and an appropriate amount of deionized water (to make the solid content 50 wt%), and stirred at 60°C for 2 h until a viscous slurry is obtained. The slurry is then placed in an oven at 300°C for drying for 6 h, taken out and ground; the slurry is then placed in a tubular furnace and heated to 1200°C at a heating rate of 5°C / min in a nitrogen atmosphere, kept at a constant temperature for 4 h, and cooled to room temperature to obtain the graphite material of this embodiment.
[0100] Example 6
[0101] (1) Calcination: Waste graphite powder was directly scraped from the negative electrode sheet of a waste battery (cylindrical 10440 battery), and was heated to 450°C at a heating rate of 5°C / min in a nitrogen atmosphere and kept at this temperature for 180 min to obtain a first precursor.
[0102] (2) Acid pickling: The first precursor was added to a 60°C acid solution (prepared by mixing 1 mol / L boric acid and hydrogen peroxide, with the mass proportion of hydrogen peroxide being 10 wt%) at a liquid-to-solid ratio of 5:1, and the mixture was acid-picked with stirring for 4 h; then filtered and washed with water until the pH value was 7, dried in an oven at 100°C, and sieved using a 300-mesh sieve to obtain a second precursor.
[0103] (3) Pre-lithiation: Take 2 wt% (based on the mass of the second precursor) of nano-scale lithium carbonate (particle size of 200 nm), add it into a ball mill together with the second precursor, and ball-mill at a speed of 300 r / min for 1 h to obtain a third precursor.
[0104] (4) Coating and carbonization: 8 wt% (based on the mass of the third precursor) of polytetrafluoroethylene is added to a magnetic stirrer together with the third precursor and an appropriate amount of deionized water (to make the solid content 50 wt%), and stirred at 60°C for 2 h until a viscous slurry is obtained. The slurry is then placed in an oven at 300°C for drying for 4 h, taken out and ground; then placed in a tubular furnace, heated to 1200°C at a heating rate of 5°C / min in a nitrogen atmosphere, kept at a constant temperature for 4 h, and cooled to room temperature to obtain the graphite material of this embodiment.
[0105] Comparative Example 1
[0106] (1) Calcination: Waste graphite powder was directly scraped from the negative electrode sheet of a waste battery (cylindrical 10440 battery), and was heated to 450°C at a heating rate of 5°C / min in a nitrogen atmosphere and kept at this temperature for 180 min to obtain a first precursor.
[0107] (2) Pickling: The calcined graphite powder was added to a mixed acid (concentration of 1 mol / L, containing nitric acid and hydrochloric acid in a volume ratio of 1:1) at 60°C at a liquid-to-solid ratio (mass ratio) of 5:1, and stirred for pickling for 4 hours; then filtered and washed with water until pH = 7, dried in an oven at 100°C for 6 hours, and sieved using a 300-mesh sieve to obtain the graphite material of this comparative example.
[0108] Comparative Example 2
[0109] (1) Calcination: Waste graphite powder was directly scraped from the negative electrode sheet of a waste battery (cylindrical 10440 battery), and was heated to 450°C at a heating rate of 5°C / min in a nitrogen atmosphere and kept at this temperature for 180 min to obtain a first precursor.
[0110] (2) Acid pickling: The first precursor was added to a 60°C acid solution (prepared by mixing 1 mol / L boric acid and hydrogen peroxide, with the mass proportion of hydrogen peroxide being 10 wt%) at a liquid-to-solid ratio of 5:1, and the mixture was acid-picked with stirring for 4 h; then filtered and washed with water until the pH value was 7, dried in an oven at 100°C, and sieved using a 300-mesh sieve to obtain a second precursor.
[0111] (3) Pre-lithiation: Take 2 wt% (based on the mass of the second precursor) of nano-scale lithium carbonate (particle size of 200 nm), add it into a ball mill together with the second precursor, and ball-mill at a speed of 300 r / min for 1 h to obtain the graphite material of this comparative example.
[0112] Comparative Example 3
[0113] (1) Calcination: Waste graphite powder is directly scraped from the negative electrode sheet of a waste battery (cylindrical 10440 battery), and is calcined in an inert atmosphere at a heating rate of 5°C / min to 450°C, and kept at this temperature for 180min to obtain a first precursor.
[0114] (2) Acid pickling: The first precursor was added to a 60°C acid solution (prepared by mixing 1 mol / L boric acid and hydrogen peroxide, with the mass proportion of hydrogen peroxide being 10 wt%) at a liquid-to-solid ratio of 5:1, and the mixture was acid-picked with stirring for 4 h; then filtered and washed with water until the pH value was 7, dried in an oven at 100°C, and sieved using a 300-mesh sieve to obtain a second precursor.
[0115] (3) Coating and carbonization: 6 wt% (based on the mass of the second precursor) of liquid polyacrylonitrile is added to a magnetic stirrer together with the second precursor and an appropriate amount of deionized water (to make the solid content 50 wt%), and stirred at 60°C for 2 h until a viscous slurry is obtained. The slurry is then placed in an oven at 300°C for drying for 6 h, taken out and ground; the slurry is then placed in a tubular furnace and heated to 1200°C at a heating rate of 5°C / min in a nitrogen atmosphere, maintained at a constant temperature for 4 h, and cooled to room temperature to obtain the graphite material of this comparative example.
[0116] Effect Example Determination of Electrochemical Performance
[0117] The graphite material, conductive carbon black SP, CMC and SBR obtained in the embodiment and the comparative example were weighed in a mass ratio of 95:2:1.5:1.5, respectively, and stirred evenly in water to form a slurry. The slurry was applied to both sides of the copper foil using an applicator, and the electrode sheet coated on both sides was placed in a vacuum drying oven at a temperature of 110°C and dried for 2 hours, and then pressed into a negative electrode (with a compaction density of 1.6 g / cm 3 ). The electrolyte composition is: EC:EMC:DNC=1:1:1 (volume ratio), containing 1 mol / L LiPF6. The counter electrode is metallic lithium. CR-2420 button cells were made in a mikaelona glove box under nitrogen conditions.
[0118] The charge and discharge test was carried out on the Blue Electric Battery Test Cabinet with a voltage range of 0.005-1.0V and a charge and discharge rate of 0.1C to obtain the first discharge capacity and the first coulombic efficiency.
[0119] The results are shown in Table 1.
[0120] Table 1
[0121]
[0122]
[0123] As can be seen from the above results, the graphite materials obtained in Examples 1-6 of the present invention can at least ensure a 0.1C capacity of not less than 370 mAh.g when used in lithium-ion batteries. -1 At the same time, the first efficiency is not less than 84%. This shows that the recovery method of the present invention can effectively reduce impurities in graphite, realize the reuse of residual inactivated lithium, and effectively repair its overall structure; thereby effectively improving the overall performance of the obtained graphite material and after being used in lithium-ion batteries.
[0124] In Comparative Example 1, compared with Example 1, without performing the pre-lithiation, coating and carbonization steps, and without doping with boron during pickling, the capacity and initial efficiency of the obtained lithium-ion battery are significantly reduced.
[0125] In Comparative Example 2, compared with Example 1, without performing the coating and carbonization steps, the capacity and initial efficiency of the obtained lithium-ion battery are significantly reduced.
[0126] In Comparative Example 3, compared with Example 1, without pre-lithiation, the capacity and first efficiency of the obtained lithium-ion battery are significantly reduced.
Claims
1. A graphite material recovery method, characterized in that: The graphite material recovery method comprises the following steps: S1. calcining graphite negative electrode powder of waste batteries to obtain a first precursor; S2, washing the first precursor with an acid solution to obtain a second precursor; Wherein, the acid solution comprises boric acid and an oxidant; S3, pre-lithiating the second precursor with a lithium salt to obtain a third precursor; S4. Coating the third precursor with a coating agent and carbonizing it to obtain the graphite material.
2. The graphite material recovery method according to claim 1, characterized in that: In step S1, the calcination is carried out under an inert atmosphere; Preferably, the inert atmosphere comprises nitrogen and / or argon; And / or, in step S1, the calcination includes a heating stage and a heat preservation stage; Preferably, the heating rate in the heating stage is 5-10°C / min; Preferably, the temperature in the insulation stage is 200-600°C, for example 450°C; Preferably, the insulation stage lasts for 60-200 min, such as 180 min.
3. The graphite material recovery method according to claim 1, characterized in that: In step S3, the lithium salt includes one or more of lithium carbonate, lithium oxalate, lithium chloride and lithium nitrate; And / or, in step S3, the mass ratio of the lithium salt to the second precursor is (0.01-0.06):1, for example 0.02:1; and / or, in step S3, the pre-lithiation comprises the step of mixing the second precursor and the lithium salt; Preferably, the mixing is performed by ball milling; the rotation speed of the ball mill is preferably 200-600 r / min, such as 300 r / min.
4. The graphite material recovery method according to claim 1, characterized in that: In step S4, the coating agent includes one or more of polyacrylonitrile, polytetrafluoroethylene and dopamine, preferably polyacrylonitrile; And / or, in step S4, the mass ratio of the coating agent to the third precursor is (0.01-0.1):1, for example, 0.02:1 or 0.06:1; And / or, in step S4, the carbonization includes a heating stage and a heat preservation stage; Preferably, the heating rate in the heating stage is 2-6°C / min, for example 5°C / min; Preferably, the temperature in the insulation stage is 1000-1300°C, for example 1200°C; Preferably, the insulation stage lasts for 4-6 hours; And / or, in step S4, the coating further includes a pre-oxidation step; Preferably, the pre-oxidation is carried out in an oven; Preferably, the pre-oxidation temperature is 200-450°C, for example 300°C; Preferably, the pre-oxidation time is not less than 6 hours; Preferably, the pre-oxidation further includes a grinding step.
5. The graphite material recovery method according to claim 1, characterized in that: In step S2, the acid solution is prepared by mixing a mixed acid and an oxidant, and the mixed acid includes boric acid; Preferably, in the mixed acid, the volume proportion of the boric acid is not less than 70%; Preferably, the mixed acid further comprises one or more of hydrochloric acid, nitric acid and sulfuric acid; Preferably, in the mixed acid, the molar concentration of the acid is 0.4-2 mol / L, such as 1 mol / L or 1.5 mol / L; And / or, in step S2, the oxidant includes hydrogen peroxide and / or potassium permanganate; And / or, in step S2, the mass ratio of the oxidant to the acid solution is (0.02-0.6):1, such as 0.1:1 or 0.2:1; And / or, in step S2, the liquid-to-solid ratio of the acid solution to the first precursor is (4-6):1, for example, 5:
1.
6. The graphite material recovery method according to claim 1, characterized in that: In step S2, the pickling temperature is 60-100°C; And / or, in step S2, the pickling time is 4-6h; And / or, in step S2, the pickling includes the step of stirring and mixing the first precursor and the acid solution; And / or, in step S2, the acid washing further includes the steps of solid-liquid separation, washing, drying and screening; Preferably, the solid-liquid separation is performed by suction filtration; Preferably, the washing is carried out with water; Preferably, the screening is performed using a sieve; the mesh size of the sieve is, for example, 300 meshes.
7. The graphite material recovery method according to claim 1, characterized in that: In step S3, the particle size of the lithium salt is 200-800 nm; And / or, in step S3, the pre-lithiation time is 0.5-4h, such as 1h or 2h; And / or, in step S4, the coating comprises the step of mixing the third precursor with the coating agent in a solvent; Preferably, the solvent comprises one or more of deionized water, ethanol and DMF; Preferably, the solid content after mixing is 40-60wt%, for example 50wt%; Preferably, the mixing is performed by stirring; Preferably, the mixing time is 2-6h; Preferably, the mixing temperature is 60-100°C.
8. A graphite material, characterized in that: The graphite material is obtained by the graphite material recovery method according to any one of claims 1 to 7.
9. The graphite material according to claim 8, characterized in that The graphite material comprises a graphite matrix, a carbon coating layer, lithium, boron and lithium boron oxide; Preferably, the graphite material satisfies one or more of the following conditions: a. The carbon coating layer is a graphene-like coating layer; b. The lithium is distributed in the graphite matrix in a free state; c. The boron is distributed in the graphite matrix in a free state; d. The lithium boron oxide is distributed on the surface of the graphite substrate.
10. Use of the graphite material according to claim 8 or 9 in an electrochemical device.
Citation Information
Patent Citations
Method for deep impurity removal and targeted repair regeneration of graphite negative electrode material from waste lithium battery negative electrode powder
CN115448308A
Regeneration and repair method for graphite negative plate of waste lithium ion battery
CN118099582A
Method for preparing lithium ion battery artificial graphite / coke anode material
CN105000545A
Regeneration method of graphite negative electrode of lithium ion battery and regenerated graphite negative electrode thereof
CN113594420A
Preparation method of micro-oxidized and pre-lithiated graphite negative electrode material and graphite negative electrode
CN117735542A